Effects of uremic solutes on reactive oxygen species in vitro model systems as a possibility of support the renal function management - Assis, Renata Pires de [UNESP]; Castro, Juliana Fernanda Almeida [UNESP]; Gutierres, Vânia Ortega [UNESP]; Arcaro, Carlos Alberto [UNESP]; Brotto, Renata Squariz [UNESP]; Oliveira, Olga Maria Mascarenhas de Faria [UNESP]; Baviera, Amanda Martins [UNESP]; Brunetti, Iguatemy Lourenço [UNESP] (Biomed Central Ltd, 2015)
Background: In view of the prevalence of oxidative stress in chronic kidney disease (CKD) patients, the loss of low-molecular-weight biomolecules by hemodialysis and the antioxidant potential of some uremic solutes that accumulate in CKD, we used in vitro model systems to test the antioxidant potential of the following uremic solutes: uric acid, hippuric acid, p-cresol, phenol, methylguanidine, L-arginine, L-tyrosine, creatinine and urea.Methods: The in vitro antioxidant efficiencies of the uremic solutes, isolated or in mixtures, were tested with the following assays: i) ABTS radical cation decolorization assay; ii) hypochlorous acid (HOCl/OCl-) scavenging activity; iii) superoxide anion radical (O-2(center dot-)) scavenging activity; iv) crocin bleaching assay (capture of peroxyl radical, ROO center dot); v) hydrogen peroxide (H2O2) scavenging activity.Results: Four of the tested uremic solutes (p-cresol, phenol, L-tyrosine, uric acid) were effective antioxidants and their IC50 were found in three model systems: ABTS(center dot+), HOCl/OCl- and crocin bleaching assay. In the 4-solutes mixtures, each one of the solute captured 12.5% for the IC50 of the mixture to ABTS(center dot+) or HOCl/OCl-, exhibiting a virtually exact additive effect. In the 2-solutes mixtures, for ROO center dot capture, it was observed the need of more mass of uremic solutes to reach an IC50 value that was higher than the projected IC50, obtained from the IC50 of single solutes (25% of each, in the binary mixtures) in the same assay. Inmodel systems for O-2(center dot-) and H2O2, none of the uremic solutes showed scavenging activity.Conclusions: The use of the IC50 as an analytical tool to prepare and analyze mixtures allows the determination of their scavenging capacities and may be useful for the assessment of the antioxidant status of biological samples under conditions of altered levels of the endogenous antioxidant network and/or in the employment and monitoring of exogenous antioxidant therapy.
Keywords: Chronic kidney disease; Hemodialysis; Oxidative stress; Uremic solutes; IC50 as clinical chemistry tool